Management strategies for natural tourism and non-timber forest products support the protection of The Gunung Leuser National Park Buffer Area in mitigating climate change - Rahmawaty; Aththorick T. Alief; Harahap R. Hamdani; Rauf Abdul; Ismail Mohd Hasmadi; Fujiwara Takahiro; Tedong Peter Aning (BIO Web of Conferences)
Gunung Leuser National Park (GLNP) is a critical conservation area with high biodiversity, providing essential ecosystem services, including climate regulation. This research aims to analyze Internal Strategic Factors (IFAS) and External Strategic Factors (EFAS) and determine appropriate strategies in the management of nature tourism and non-timber forest products to support the protection of the GLNP buffer area in climate change mitigation. This research uses SWOT analysis and Focus Group Discussions (FGD). The research results show an IFAS of 0.82 and an EFAS 1.55. The final IFAS and EFAS scores based on the SWOT diagram are in Quadrant I, indicating that strengths and opportunities are high, and weaknesses and threats are low in terms of managing natural tourism and non-timber forest products to support the protection of the GLNP in mitigating change climate. The research highlights the importance of involving local stakeholders, implementing community-based conservation initiatives, and leveraging traditional knowledge to foster sustainable practices. The findings suggest that a balanced approach, combining conservation efforts with economic incentives, is vital for enhancing the resilience of GLNP’s buffer zones against climate change impacts. This study contributes to the broader discourse on climate change mitigation by offering actionable strategies for sustainable development.